A Biopredictive In Vitro Comparison of Oral Locally Acting Mesalazine Formulations by a Novel Dissolution Model for Assessing Intraluminal Drug Release in Individual Subjects - Karkossa, Frank; Klein, Sandra (Journal of pharmaceutical sciences, 2018)
Drug release and availability at the site of action are the major factors determining the clinical response for locally-acting gastrointestinal (GI) drug products. The present work focused on the prediction of site and extent of in vivo mesalazine release after oral administration to a variety of subjects using individualized in vitro drug release experiments. First, experiments mimicking GI passages in average adult subjects were performed. Then, results from a study screening fasted in vivo pH and transit profiles in individual subjects were translated into a novel in vitro dissolution model enabling to mimic individual GI pH-profiles and transit times with physiologically relevant dissolution media. A selection of monolithic and multiparticulate mesalazine formulations with pH-dependent and pH-independent drug release was screened with the novel dissolution model. Results of the study indicate that dosage form performance can be significantly different in individual subjects and highlight the importance of addressing individual physiological parameters relevant to intraluminal drug release when the aim is to predict the in vivo performance of locally-acting mesalazine formulations in individual patients. The novel in vitro dissolution approach thus represents a valuable tool for both improving individual oral therapy with locally-acting GI drug products and assessing bioequivalence of these formulations.